Movie adaptations as a factor in the selection of fiction books in selected private high school libraries in Quezon City - Lim, Sharisse Rae T. (2012)
Traditionally, reading about both real and fictitious people, places, times, and events, gave young adults the chance to widen their understanding of life. However, times are changing and various mass media like television and movies have taken over their interests and reading has become an afterthought "Since not all youth like to read, movies, television programs, and games can be a launch point for a discussion about story" (Gallaway, 2010)